2014
DOI: 10.15623/ijret.2014.0306016
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Partial Purification and Characterization of Alkaline Serine Protease From Seeds of Cucumis Melo Var Agrestis

Abstract: The present study shows the isolation, partial purification and characterization of alkaline protease from the seeds of Cucumis melo var agrestis, by a four step purification process. Its molecular weight was estimated to be 54KDa. Enzyme showed maximum activity at p H 9.0 and optimum temperature at40 o Cwith casein as substrate. The enzyme exhibited homogeneity as attested by a single protein band on both native PAGE and SDS PAGE. It is a monomeric enzyme and nonglycoprotein in nature. The k m value of enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…Most plant proteases are known to be active over a wide range of pH and temperature values. These results are in good agreement with the results obtained from Gliricidia sepium seeds (da Silva et al, 2020), green chickpea seeds (Banik et al, 2018) from Canavalia ensiformis seeds (Gonçalves, Gozzini Barbosa, & Silva-López, 2016), Cucumis melovaragrestis seeds (Devi & HemaLatha, 2014) and Black gram seeds, Lentil seeds and Green gram seeds (Anupama, Marimuthu, Sundaram, & Gurumoorthi, 2013). The excellent activity and stability over wide pH range shows that the alkaline nature of the protease, which makes it suitable for use in alkaline environments and with detergents (Zanphorlin et al, 2010).…”
Section: Determination Of the Optimum Phsupporting
confidence: 87%
See 2 more Smart Citations
“…Most plant proteases are known to be active over a wide range of pH and temperature values. These results are in good agreement with the results obtained from Gliricidia sepium seeds (da Silva et al, 2020), green chickpea seeds (Banik et al, 2018) from Canavalia ensiformis seeds (Gonçalves, Gozzini Barbosa, & Silva-López, 2016), Cucumis melovaragrestis seeds (Devi & HemaLatha, 2014) and Black gram seeds, Lentil seeds and Green gram seeds (Anupama, Marimuthu, Sundaram, & Gurumoorthi, 2013). The excellent activity and stability over wide pH range shows that the alkaline nature of the protease, which makes it suitable for use in alkaline environments and with detergents (Zanphorlin et al, 2010).…”
Section: Determination Of the Optimum Phsupporting
confidence: 87%
“…therefore, its value serves to characterize a particular enzyme-substrate system under certain specific conditions. A Lineweaver-Burk plot for casein was linear suggesting that the rate of proteolysis was The Km value of the present report is also lower than reported by other workers obtained from protease enzymes of some other plants like field bean seeds enzyme 0.0105M (Paul & Gowda, 2000), 0.107M from Moringa oleifera leaves (Banik et al, 2018), 0.02M from the seeds of Cucumismelovaragrestic (Devi & HemaLatha, 2014) and 0.19M from Yemeni bean seeds (Maqtari, Naji, & Ali). However, the value of Vmax is higher in the present study as reported in Table 3 than those of calculated from Sorghum malt protease which was 8.2 μmol/minute (Ogbonna & Okolo, 2005), Mentha piperita L protease, 2.94 μmol/minute and Thymus capitatus L protease 1.3 μmol/minute (Atrooz & Alomari, 2020).…”
Section: Determination Of Km and Vmaxcontrasting
confidence: 72%
See 1 more Smart Citation
“…The previous result differs greatly, which might be attributed to the type of cultivars and the maturation of the pineapples (Ding and Syazwani, 2015;Ferreira et al, 2016). In addition, the purity of the bromelain might also contribute to the antioxidant level (Devi and HemaLatha, 2014;Saptarini et al, 2019a). The IC50 value of UFB was lower than that of PPB.…”
Section: Antioxidant Activitymentioning
confidence: 78%
“…The purification fold of PPB was decreased with a folding of 0.20, whereas UFB has a purification fold of 3.25. Principally, the purification fold should increase more than one after the purification method has been applied (Devi and HemaLatha, 2014). A low purification fold suggests salt interference in the solution.…”
Section: Purification Yield and Enzymatic Activitymentioning
confidence: 99%